Electrospun magnetic carbon composite fibers: Synthesis and electromagnetic wave absorption characteristics. Issue 6 (31st May 2012) - Yang, Ying; Guo, Zhen; Zhang, Huan; Huang, Daqing; Gu, Jialin; Huang, Zhenghong; Kang, Feiyu; Alan Hatton, T.; Rutledge, Gregory C.
Abstract Electrospun polyacrylonitrile (PAN)‐based carbon composite fibers embedded with magnetic nanoparticles have been developed as materials for electromagnetic wave absorption. The nanocomposite fibers were prepared by electrospinning from a dispersion of magnetite (Fe3O4) nanoparticles stabilized by L‐glutamic acid in a solution of PAN and N, N‐dimethyl formamide. The Fe3O4‐embedded PAN nanofibers were stabilized at 270°C in air and carbonized at 800°C in nitrogen. The Fe3O4 nanoparticles were crystalline with a particle size of about 7 nm, most of which was reduced to Fe3C with agglomerates of up to 50 nm diameter in the carbon fibers. The carbon morphology was mostly disordered, but exhibited a layered graphitic structure in the vicinity of the nanoparticles. The carbon composite fiber exhibited ferromagnetic behavior, and the induced magnetic saturation per unit mass of fibers increased with increasing Fe3O4 content in the precursor. The complex relative dielectric permittivity was tuned by adjusting the amount of Fe3O4 in the carbon fiber precursor. With increasing Fe3O4 content, good electromagnetic wave absorption characteristics were observed below 6 GHz, even for samples with fiber loadings as low as 5 wt %. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013